A Relativistic Double Neutron Star Binary PSR J1846-0513 - D. Zhao; N. Wang; J. P. Yuan; D. Li; P. Wang; M. Y. Xue; W. W. Zhu; C. C. Miao; W. M. Yan; J. B. Wang; J. M. Yao; Q. D. Wu; et al. (The Astrophysical Journal Letters, 2024)
We report the timing analysis of PSR J1846−0513, a pulsar discovered by the Five-hundred-meter Aperture Spherical radio Telescope (FAST) in Commensal Radio Astronomy FAST Survey. The pulsar possesses a spin period of 23.36 ms and a spin-down rate ( $\dot{P}$ ) of 1.0106(3) × 10 ^−18 s s ^−1 , and it is located in an eccentric orbit ( e ∼0.208) with an orbital period of 0.61 days. The characteristic age and surface magnetic field of the pulsar are found to be 366.62 Myr and 4.9178 × 10 ^9 G, respectively, indicating that it is a recycled pulsar. Using over two years of timing data, we measure the periastron advance $\dot{ω }$ = 0.8956(8) deg yr ^−1 . By assuming that this effect is purely relativistic, we have estimated the total mass M = 2.6287(35) M _⊙ and obtained an upper limit for the pulsar mass and a lower limit for the companion’s mass. Our results indicate that this is a double neutron star system.